Feasibility of biomass heating system in Middle East Technical University, Northern Cyprus Campus. Issue 1 (31st December 2016) - Asumadu-Sarkodie, Samuel; Owusu, Phebe Asantewaa
Abstract: Global interest in using biomass feedstock to produce heat and power is increasing. In this study, RETScreen modelling software was used to investigate the feasibility of biomass heating system in Middle East Technical University, Northern Cyprus Campus. Weiss Kessel Multicratboiler system with 2 MW capacity using rice straw biomass as fuel and 10 units of RBI® CB0500 boilers with 144 kW capacity using natural gas as fuel were selected for the proposed biomass heating system. The total cost of the biomass heating project is US 786, 390. The project has a pre-tax and after tax internal rate of return (IRR) of 122.70%, simple payback period of 2.54 years, equity payback period of 0.83 year, a net present value of US 3, 357, 138.29, an annual lifecycle savings of US 262, 617.91, a benefit-cost ratio of 21.83, an electricity cost of 0/kWh and a GHG reduction cost of −204.66 /tCO₂. The annual GHG emission reduction is 1, 283.2 tCO₂, which is equivalent to 118 hectares of forest absorbing carbon. The development and adoption of this renewable energy technology will save costs on buying conventional type of heating system and result in a large technical and economic potential for reducing greenhouse gas emissions which will satisfy the sustainable development goals.